(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2025)
The adolescent growth stage is a phase in human life that requires serious attention. This is because there are many changes during adolescence, starting from physical, social and emotional. Sufficient energy intake and regular exercise habits are the keys to good change. However, this is often overlooked by adolescents. Inderalaya is a sub-district located not far from the provincial capital. The influence of modernization has made adolescents living in the area feel the impact, both in terms of diet and physical activity. This study aims to determine the relationship between energy intake, exercise habits and nutritional status in adolescents in Inderalaya. This study is descriptive analytical with a cross-sectional design. The number of subjects involved was 110 people. The location of the study was at SMP Negeri 1 Inderalaya. The data that had been collected was processed using SPSS statistical software vers.25 and analyzed using the Spearman correlation test. The results showed that the age of the subjects was in the range of 12 to 15 years. Subjects with male gender (51.8%) were selected slightly more than subjects with female gender (48.2%). The subjects’ energy intake was mostly deficit, while the subjects’ exercise habits were less active. Although the subjects’ nutritional status was dominated by normal nutritional status (51.8%), the proportion of overnutrition also had a fairly high percentage (45.5%). The results of the bivariate analysis showed that there was no relationship between energy intake, exercise habits and nutritional status (p>0.05). It is necessary to involve other variables in the future to see the determinants of nutritional status in adolescents. The suggestion of this study, although no significant relationship was found, subjects still need to take the time to exercise and consume nutritious food to avoid nutritional deficiencies.